Implementasi System Usability Scale pada Sistem Informasi Rencana Umum Pengadaan (SIRUP) Lokal Pemerintah Provinsi Jawa Tengah - Slamet Riyanto; Yohanes Suhari (Elkom: Jurnal Elektronika dan Komputer, 2024)
Sistem Informasi Rencana Umum Pengadaan (SIRUP) Lokal is a web-based application utilized by the Government of Central Java Province for procurement planning of goods and services. Of course, evaluation is needed to measure the usability level of the SIRUP Lokal and as input for future development purposes. The respondents of this research are active users of SIRUP Lokal, totaling 100 people. This research is quantitative in nature with descriptive analysis. Data collection is done through questionnaires. Data processing and analysis utilize statistical tools, namely SPSS. The results of this research indicate that SIRUP Lokal is perceived to be highly beneficial for users, especially 1) The system’s performance is considered superior, excelent, and well-received by users 2) Users tend to recommend the system to others.